AMERICAN PERCEPTIONS ON BARRIERS OF LEARNING INDONESIAN AS A FOREIGN LANGUAGE - Syahri, Chaidir; Isnendes, Retty; Muniroh, R. Dian Dia-an (International Journal of Education, 2024)
Foreign language acquisition is one of the important issues in the current era of globalization. Indonesian is not an exception because, within the last twenty years, the significance of Indonesian language has increased. This study aims to reveal the problem of the learning of Indonesian language as a foreign language. It focused on adolescent learners from the United States of America in a reputable language institution. More specifically, there are two questions in this study. First, what are the barriers of learning Indonesian that were found by the American learners? Second, what are the types of teaching materials that these learners like? This study is a case study with descriptive methods. It was conducted in a training institution focusing to train Christian preachers. Four learners from the United States of America were the informants in this study. The data were generated from the four American learners in obtained through (1) observation; (2) depth interviews with informants; and (3) relevant documents. This study concluded that (1) in general, the barriers faced by the American learners can be classified into four types: social, mental, phonological, and grammatical; and (2) the learners prefer various teaching materials but their common preference is the authentic learning materials that consider aspects of audiovisual media use, Indonesian cultural diversity, and language formality. Since the study only relied on four informants, the results cannot be generalized to all learners of Indonesian Language. However, they can provide a figure in the learning of Indonesian language involving non-native speakers, especially the Americans.